Formation, Clearance, Deposition, Pathogenicity, and Identification of Biopharmaceutical-related Immune Complexes: Review and Case Studies. (June 2014) - Rojko, Jennifer L.; Evans, Mark G.; Price, Shari A.; Han, Bora; Waine, Gary; DeWitte, Mark; Haynes, Jill; Freimark, Bruce; Martin, Pauline; Raymond, James T.; Evering, Winston; Rebelatto, Marlon C.; et al.
Vascular inflammation, infusion reactions, glomerulopathies, and other potentially adverse effects may be observed in laboratory animals, including monkeys, on toxicity studies of therapeutic monoclonal antibodies and recombinant human protein drugs. Histopathologic and immunohistochemical (IHC) evaluation suggests these effects may be mediated by deposition of immune complexes (ICs) containing the drug, endogenous immunoglobulin, and/or complement components in the affected tissues. ICs may be observed in glomerulus, blood vessels, synovium, lung, liver, skin, eye, choroid plexus, or other tissues or bound to neutrophils, monocytes/macrophages, or platelets. IC deposition may activate complement, kinin, and/or coagulation/fibrinolytic pathways and result in a systemic proinflammatory response. IC clearance is biphasic in humans and monkeys (first from plasma to liver and/or spleen, second from liver or spleen). IC deposition/clearance is affected by IC composition, immunomodulation, and/or complement activation. Case studies are presented from toxicity study monkeys or rats and indicate IHC-IC deposition patterns similar to those predicted by experimental studies of IC-mediated reactions to heterologous protein administration to monkeys and other species. The IHC-staining patterns are consistent with findings associated with generalized and localized IC-associated pathology in humans. However, manifestations of immunogenicity in preclinical species are generally not considered predictive to humans.